A recombinant Modified Vaccinia virus Ankara expressing prME of tick-borne encephalitis virus affords mice full protection against TBEV infection - Kubinski, Mareike; Beicht, Jana; Zdora, Isabel; Biermann, Jeannine; Puff, Christina; Gerlach, Thomas; Tscherne, Alina; Baumgärtner, Wolfgang; Osterhaus, Albert D. M. E.; Sutter, Gerd; Prajeeth, Chittappen Kandiyil; Rimmelzwaan, Guus F. (Frontiers in Immunology, 2023)
Tick-borne encephalitis virus (TBEV) is an important human pathogen that can cause serious disease involving the central nervous system (tick-borne encephalitis, TBE). Although approved inactivated vaccines are available, the number of TBE cases is rising and breakthrough infections in fully vaccinated subjects have been reported in recent years. In the present study, we generated and characterized a recombinant Modified Vaccinia virus Ankara (MVA) for the delivery of the pre-membrane (prM) and envelope (E) proteins of TBEV (MVA-prME). MVA-prME was tested in mice in comparison with a licensed vaccine FSME-IMMUN® and proved to be highly immunogenic and afforded full protection against challenge infection with TBEV. Our data indicate that MVA-prME holds promise as an improved next generation vaccine for the prevention of TBE.